2011
DOI: 10.1002/eji.201040886
|View full text |Cite
|
Sign up to set email alerts
|

Early viral replication in lymph nodes provides HIV with a means by which to escape NK‐cell‐mediated control

Abstract: Acute HIV infection is marked by dramatic viral replication associated with preferential replication within secondary lymphoid tissues, such as lymph nodes (LNs), that is rapidly but incompletely contained to a viral setpoint. Accumulating evidence supports a role for natural killer (NK) cells in the early control of HIV infection; however, little is known about the location of their antiviral control. Given that HIV replicates profusely in LNs during early infection, we sought to define whether changes occurr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…How might ADCC contribute to CD4 + T-cell destruction in vivo, particularly in light of differences in the tissue distribution of CD4 + T cells and natural killer (NK) cells, the mediators of ADCC? HIV-1 replication primarily happens in lymphoid tissues, where up to 95% of CD4 + T cells reside ( Pantaleo et al, 1994 ), yet only a small fraction of ADCC-competent CD56 dim CD16 + NK cell population is distributed within lymph nodes ( Luteijn et al, 2011 ). We hypothesize that NK cells contribute to bystander killing during the transit of CD4 + T cells between lymph nodes, the lymphatic system and the blood, where CD56 dim CD16 + NK cells are present in large quantities and could mediate efficient ADCC against gp120-coated cells ( Artis and Spits, 2015 , Fauci et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…How might ADCC contribute to CD4 + T-cell destruction in vivo, particularly in light of differences in the tissue distribution of CD4 + T cells and natural killer (NK) cells, the mediators of ADCC? HIV-1 replication primarily happens in lymphoid tissues, where up to 95% of CD4 + T cells reside ( Pantaleo et al, 1994 ), yet only a small fraction of ADCC-competent CD56 dim CD16 + NK cell population is distributed within lymph nodes ( Luteijn et al, 2011 ). We hypothesize that NK cells contribute to bystander killing during the transit of CD4 + T cells between lymph nodes, the lymphatic system and the blood, where CD56 dim CD16 + NK cells are present in large quantities and could mediate efficient ADCC against gp120-coated cells ( Artis and Spits, 2015 , Fauci et al, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional impairment of NK cells during progressive HIV or SIV infection also includes diminished antibody-dependent cellular cytotoxic (ADCC) function (14,15) and cytokine secretion (16,17), whereas chemokine secretion is unaffected (9,18). Lymph node (LN) NK cells, conversely, become more activated during HIV infection (19).…”
Section: The Accumulation Of Cd16mentioning
confidence: 99%
“…During progressive HIV-1 infection NK cell mucosal distribution is altered [54]. In lymph nodes [14], acute HIV-1 infection does not change the numbers or distribution of NK cell subsets as compared to healthy individuals [74], with KIR -NK cells being the major NK cell subset. This finding is explained by a decreased capacity of KIR + and KIR -NK cells for homing to LN.…”
Section: Control Of Hiv-1 Infection By Nk Cellsmentioning
confidence: 98%
“…Nevertheless, LN KIR -NK cells are highly activated and express TRAIL [74]. The decreased homing capacity of cytotoxic KIR + NK cells offers an additional opportunity for HIV-1 to escape a control of viral replication and to establish long-term infection in LN [74]. It has been suggested that NK cells from EC or LTNP resist anergy [75].…”
Section: Control Of Hiv-1 Infection By Nk Cellsmentioning
confidence: 99%